Combined amiodarone and digitalis therapy before heart transplantation is associated with increased post‐transplant mortality. (1st July 2020) - Rivinius, Rasmus; Helmschrott, Matthias; Rahm, Ann‐Kathrin; Darche, Fabrice F.; Thomas, Dierk; Bruckner, Tom; Doesch, Andreas O.; Ehlermann, Philipp; Katus, Hugo A.; Zitron, Edgar
Abstract: Aims: Amiodarone and digitalis are frequently used drugs in patients with heart failure. Both have separately been linked to reduced post‐transplant survival, but their combined impact on mortality after HTX remains uncertain. This study investigated the effects of combined amiodarone and digitalis use before HTX on post‐transplant outcomes. Methods and results: This registry study analysed 600 patients receiving HTX at Heidelberg Heart Center between 1989 and 2016. Patients were stratified by amiodarone and digitalis use before HTX. Analysis included patient characteristics, medication, echocardiographic features, heart rates, permanent pacemaker implantation, atrial fibrillation, and post‐transplant survival including causes of death. One hundred eighteen patients received amiodarone before HTX (19.7%), hereof 67 patients with digitalis (56.8%) and 51 patients without digitalis before HTX (43.2%). Patients with and without amiodarone before HTX showed a similar 1 year post‐transplant survival (72.0% vs. 78.4%, P  = 0.11), but patients with combined amiodarone and digitalis before HTX had a worse 1 year post‐transplant survival (64.2%, P  = 0.01), along with a higher percentage of death due to transplant failure ( P  = 0.03). Echocardiographic analysis of these patients showed a higher percentage of an enlarged right ventricle ( P  = 0.02), left atrium ( P  = 0.02), left ventricle ( P  = 0.03), and a higher rate of reduced left ventricular ejection fraction ( P  = 0.03). Multivariate analysis indicated combined amiodarone and digitalis use before HTX as a significant risk factor for 1 year mortality after HTX (hazard ratio: 1.69; 95% confidence interval: 1.02–2.77; P  = 0.04). Conclusions: Combined pre‐transplant amiodarone and digitalis therapy is associated with increased post‐transplant mortality.